(untitled) (Archeomatica, 2023)
The integration of storytelling and gamification in cultural communication and education offers a powerful means to engage audiences and make cultural content more accessible and enjoyable. The Cultrip project exemplifies how these methodologies can be successfully implemented, providing an interactive and educational experience for children at the Colosseum archaeological park. By embracing innovative approaches, cultural institutions can foster a deeper appreciation and understanding of heritage among diverse audiences, ultimately contributing to the democratization of culture and knowledge.